Anscombe reading Aristotle - Susana Cadilha (Enrahonar: Quaderns de Filosofia, 2020)
Under one particular reading of it, Anscombe’s ‘Modern Moral Philosophy’ is considered a seminal text in the revival of virtue ethics. Seen thus, Anscombe is implying that it is possible to do ethics without using concepts such as ‘moral ought’ or ‘moral obligation’, the perfect example being Aristotelian ethics. On the other hand, Anscombe claims that it is not useful at present to engage in moral philosophy since she finds that ‘philosophically there is a huge gap… which needs to be filled by an account of human nature, human action, …and above all of human “flourishing”’ (Anscombe, 1958: 18). The gap Anscombe refers to appears where there should be a ‘proof that an unjust man is a bad man’. My aim in this paper is to discuss the various ways in which Anscombe’s theses can be interpreted, recalling two other philosophers for whom Aristotelian virtue ethics was also essential: P. Foot and J. McDowell. I will argue that Anscombe did not expect Aristotelian ethics to answer the problems modern ethics poses.